Cognitive And Affective Dimension Of Critical Thinking To Student Engagement Among Nursing Students In Rizal Province - Ponciano, Dovie B.; Aliswag, Emerson G. (Journal of Neonatal Surgery, 2025)
Background: Critical thinking is a key nursing competency that allows nurses to deal with the intricacies of healthcare issues, e.g., lack of resources and heterogeneity of patient needs, maintaining quality care. It has a close relationship with problem-solving, as Garcia and Lopez (2022) underscore. Despite this, some barriers prevent the production of critical thinking among nurses in training, i.e., prevailing rote memorization, lack of adequate exposure to actual clinical situations, and poor evaluation practices (Cruz, 2020). Moreover, Acain et al. (2020) emphasize the importance of the clinical learning environment, whereas Lee et al. (2020) and Capistrano & Rubio (2022) prove the efficacy of blended and simulation-based learning in developing critical thinking. Cultural beliefs, for example, respect for authority and obedience can also deter students from challenging current practices (Hofstede Insights, 2023). In addition, David and Macatangay (2020) propose that disposition towards critical thinking among students will affect academic success. The study aims to address the gap in research on dimensions of critical thinking among young Filipino nursing students through the exploration of factors that affect its development and student participation. Finally, the results will help enhance the quality of nursing education and patient care in the country. Result: The critical thinking is an essential skill for the nurses, as it allows them to address the complex issues for the patients in healthcare facilities, make appropriate clinical decisions, and offer a high-quality care to patients. Various studies indicate a several factors affecting the critical thinking acquisition, such as teaching approaches, clinical learning settings, and culture. The use of the traditional rote memorization and insufficient exposure to the actual clinical situations inhibits the development of the critical thinking, whereas blended and simulation-based learning have been proven to be an effective in developing the analytical skills. Students' disposition towards the critical thinking and school participation also plays an important role in the whether they can implement a reasoning and problem-solving in practice. With these considerations, the developing critical thinking competencies among the nursing students are not only important for maximizing the patient outcomes but also for the growth of the nursing profession. Conclusion: the study necessitates an integrative strategy in nursing education that encompasses the emotional resilience, intellectual curiosity, and behavioral consistency. Specifically, the targeted the interventions, such as curricular adjustments and active engagement of the Nursing Clinical Instructors and Professors, are critical in transposing the theoretical learning into a realistic practice. Enhancing these aspects will improve the production of the well-rounded nursing professionals who are ready for the realities of today's healthcare setting.